PEMBELAJARAN KOOPERATIF TIPE COURSE REVIEW HORAY DALAM PROSES BELAJAR MATEMATIKA PADA ANAK TUNAGRAHITA RINGAN DI SLB - AFIFAH, NUR (Jurnal Pendidikan Khusus, 2017)
ABSTRACT Learning mathematics was a process of learner’s change with his/her learning environment discussing about numbers and the counting. Mentally retardation children had intellectual hindrance which had impact to learning problem as difficulty in thinking abstractly, whatever learning should behave concrete such as in academic domain. Therefore, to solve the problem of mentally retardation children in learning mathematics process it was given fun learning model i.e. cooperative learning model of course review horay type. This research had purpose to analyze whether there was influence of learning cooperative model of course review horay in learning mathematics to mild mentally retardation children in SLB C Dharma Wanita Lebo Sidoarjo or not. The kind of research used was pre-experiment. The design used one group pre test post test. The method used to collect the data was test method and documentation method. For data analysis, the research used the analysis technique of statistic non parametric with 6 children as subject. From the result of data analysis it was indicated that the average value of pre test was 45 and the average value of post test was 83. The research result after giving cooperative learning of course review horay type indicated that zh = 2,05 > Zt = 1,96. It indicated “there was significant influence of cooperative learning model of course review horay type in learning mathematics to mild mentally retardation children in SLB C Dharma Wanita Lebo Sidoarjo”.   Keywords : mathematics, cooperative learning of course review horay type